Longitudinal Association Among Internet Addiction, Cyberbullying Victimization and Quality of Life Among Children: Is Parental Mediation a Protective Factor? - Ding, Ning; Li, Chunkai (Child & Family Social Work, 2026)
This study aims to examine the direct and indirect relationship between internet addiction and quality of life through the mediating role of cyberbullying victimization and the moderating role of parental mediation and gender using a two‐wave longitudinal design with a 6‐month interval. A total of 649 students graded 6 to 9 participated in this research, comprising 47.5% males and 52.5% females. The results showed that internet addiction negatively predicted quality of life (β = −0.093, p = 0.032), and cyberbullying victimization (β = −0.014, p = 0.033, 95%CI [−0.020, −0.001]) partly mediated this negative association. Unexpectedly, restrictive mediation may exacerbate the negative impact of internet addiction on quality of life (β = −0.086, p = 0.019). Active mediation (β = 0.076, p = 0.036) and restrictive mediation (β = 0.098, p = 0.009) could both mitigate the negative effects of cyberbullying victimization on quality of life. Finally, results showed that females are more vulnerable to poor quality of life (βmale = 0.001, p = 0.991; βfemale = −0.201, p = 0.001) and increased levels of cyberbullying victimization (βmale = 0.036, p = 0.561; βfemale = −0.231, p < 0.001) induced by internet addiction compared to males. These results underscore the proliferating process of internet‐related risks and their potentially adverse influences, elucidating the protective influence of various forms of parental mediation and delineating gender‐specific differences within these relationships. Policymakers, social workers and parents can take measures to disrupt the proliferation of internet‐related risks, provide gender‐sensitive training interventions and focus on parental active mediation to protect children from internet addiction and cyberbullying victimization.